Treatment non-compliance with antipsychotics in Pakistan - Zahra Aamir Khan; Iman Ishfaq; Tooba Jabeen (Journal of the Pakistan Medical Association, 2025)
Psychosis refers to symptoms affecting the mind due to loss of contact with reality. It can disrupt a person’s thoughts and they might experience hallucinations or delusions. This altered sense of reality can significantly affect everyday activities and the ability to maintain relationships. Psychosis is not a diagnosis, rather a symptom of various mental health conditions. About one in every 150 individuals is affected by psychotic disorders at least once in their lifetime.1 Antipsychotics are used to control psychotic symptoms and the duration of the therapy depends on the severity of illness. For short-term psychoses such as delirium, medications are continued for two additional weeks after symptoms resolve and then tapered off gradually. With chronic schizophrenia, antipsychotics are usually taken permanently to avoid recurrence.2 However, in countries such as Pakistan, where with low literacy and social stigma associated with mental illnesses, many patients discontinue their antipsychotic therapy due to various factors.3 Many of these reasons have been discussed by Rao et al4, including patient-related, and healthcare system-related factors. Denial, lack of awareness, financial constraints, adverse effects of the medicines, and complex regimens, all contribute to patients’ non-adherence. Insufficient training of doctors, poor patient management, and long waiting times for appointments can contribute to a poor doctor-patient relationship, which leading to negative patient outcomes. One important factor is the side effect profile of antipsychotics. They can cause extrapyramidal effects like akathisia, parkinsonism, dystonia, and tardive dyskinesia. Weight gain, sedation, blurring of vision, postural hypotension, prolactin elevation, and constipation are also common.5 Such effects make it difficult to continue therapy without seriously affecting the lifestyle of patients. Discontinuation prevents patients from fully benefiting from the medication, leading to persistent or recurrent psychosis. Hence it is of utmost importance for the Pakistani healthcare system to come up with a method that ensures continuation of therapy among our population. Healthcare providers should patients to join relevant support groups to help them cope with the emotional aspects of their illness. Although developing medications with fewer side effects is challenging, it could help address one of the most common reasons for non-adherence. Further research is needed to address the factors contributing to non-adherence.